THE INFLUENCE OF WORKING DISCIPLINE AND JOB DESCRIPTION OF PERFORMANCE OF EMPLOYEE IN REGIONAL REVENUE OFFICE - Rafian Joni (University of Sang Bumi Ruwa Jurai, 2020)
The hypothesis in this study is that there is an influence of work discipline and job descriptions both partially and simultaneously on employee performance.The population in this research were 47 employees, the sample used in this study amounted to 46 employees. Data collection techniques include observation, documentation and questionnaires. Methods of data analysis using qualitative and quantitative approaches with the help of statistical tools SPSS version 21.0 include the calculation of the validity test, reliability test, regression test and the coefficient of determination test.The results of testing the hypothesis of the influence of work discipline on performance partially shows that work discipline has a positive influence on performance with a contribution of 73.9%. Other partial Hypothesis Testing, obtained job description results have a positive influence on performance with a contribution of 62.9%. Simultaneous hypothesis testing shows that work discipline and job descriptions together have a positive influence on performance with a contribution of 74.1%, while the remaining 25.9% is a variation of other variables not examined.